Ensuring safety requirement to home food and home restaurant: focus on a regional experience based on sector legislation, and future perspectives - Marzocca, P.; Daleno, D.; Orsi, G. B.; Napoli, C.; Marcotrigiano, V. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
The sharing economy provides many new business opportunities, particularly in local areas where culinary traditions guarantee major appreciable sensorial features. In this context, home food and home restaurant find their place. The first one refers to businesses that, in a home kitchen or in premises used mainly as a private home, produce food for retail, while the second one is defined as food businesses producing and administering food and beverages in a private dwelling house. This manuscript analyses the sector legislation applicable to these new business forms, the adherence to the requirements prescribed by the recent guidelines, the executive compliance applicable to the inspection phases, as well as the perspectives and future challenges that healthcare workers designated for food safety official controls will face.